Bihar Second Five-Year Plan Progress Report for the Period Ending December 1958 - Planning Commission (Planning Commission, 1958)
Agricultural Production Minor Irrigation Soil Conservation Land Development Marketing Animal Husbandry Dairying and Milk Supply if) Forest Fisheries, C. P. and N. E. S
Bihar